2020
DOI: 10.1002/fsn3.1485
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic and dietary diversity characteristics are associated with anemia among pregnant women attending antenatal care services in public health centers of Kembata Tembaro Zone, Southern Ethiopia

Abstract: Anemia affects every country in the world including Ethiopia. It costs the socio-economic developments due to its health impacts. This study was aimed to determine socio-demographic and dietary diversity and other factors associated with anemia among pregnant women in Kembata Tembaro Zone. Institution-based cross-sectional study design was employed. Data were collected from 423 pregnant women.Hemoglobin level was measured by Hemocue. Pretested interviewer-administered close-ended questionnaire was used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
5
20
1
1
Order By: Relevance
“…Similar to this finding, a study from Rwanda showed that women belonging to middle and rich wealth status were 17 and 26 per cent less likely to be anaemic compared to poor women respectively (Hakizimana et al, 2019). Women having formal education tended to be less likely to have anaemia prevalence in Ethiopia compared to those women who had no formal education which was similar to this study (Samuel et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to this finding, a study from Rwanda showed that women belonging to middle and rich wealth status were 17 and 26 per cent less likely to be anaemic compared to poor women respectively (Hakizimana et al, 2019). Women having formal education tended to be less likely to have anaemia prevalence in Ethiopia compared to those women who had no formal education which was similar to this study (Samuel et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Another study showed age and ethnicity of women were the significant predictors of anaemia prevalence (Aljaadi et al, 2019). Rural women who went for antenatal appointments were noticed more likely to have anaemia than those who resided in urban areas in Ethiopia (Belay et al, 2019;Samuel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The current result agrees with studies from Arsi Zone, Ethiopia which was 50.26%, 28 whereas it was higher than the prevalence reports from Bale Zone, Ethiopia 44.8%, 29 Shashemene Oromia, Ethiopia 25.4%, 7 East Gojam Zone, Ethiopia 45%, 12 West Gojam, Northwest Ethiopia 46.4% 30 and Ghana 40.3%. 31 On the other hand, it was lower than the observations reported from the public health facility of Nekemte town (73.11%), 32 Kembata Tembaro public health centre southern Ethiopia (79.9%), 33 Alamata General Hospital of Tigray Ethiopia (61.2%) 14 and Islamabad, Pakistan (89%). 34 All these discrepancies might be because of the variations in the dietary diversity score measurement tools, and geographical and seasonal variations.…”
Section: Discussionmentioning
confidence: 66%
“…Higher educational status of the household head was significantly associated with higher dietary diversity scores, which may be due to improved nutritional awareness in the household (26) . Farmer as family heads' occupation had a significant association with low HDD scores.…”
Section: Demographic Determinants Of Household Dietary Diversitymentioning
confidence: 95%